(untitled) (Herald of Journalism, 2020)
The article examine the importance of creating special effects and com- puter video editing. Also as the creation of the video – the releationship between partners. To make TV programs are creative work. Theoretically hand-writing the script, prepare texts, decorate the melody – is concept of the products. The Advantage of the fact that today the industrial-innova- tive development has proved to be a new way of world competition act and science. TV project activity of Euro Median culture, creative ability, free technology tendency progressively expand science and knowledge gave conceptiative solutions. Including methods of TV design talks about the importance of convergent journalist.